Modern Approaches to Administration of Long-Term Science- Intensive and High Technology Projects - Volodin, Sergei V.; Bunak, Valeriy A.; Volodina, Svetlana; Nedbaylo, Nikolay Yu.; Ilyahinskaya, Galina V. (The journal of contemporary issues in business and government, 2021)
The article introduces a novel and relevant research methods which were based on the most topical principles of project management, focused on effective time, price, and final results management. The aim of the following article is to highlight the peculiarities of the modern approaches to the administration of long-lasting science-intensive and hi-tech projects that distinguish these projects from the traditional methods. Special attention was given to the methodology of such managerial aspects as substantiation of the system-forming principles, placed in the root model of administration of long-term scientific-intensive and hi-tech projects and development of roadmaps by the creation stages of scientific-intensive processes, including the maintenance events and corresponding documents for each stage. As a result, the groups of hard and soft factors were revealed incoherence to project management influence factors. Also, the role functions and distribution of responsibility of members of scientifically-intensive projects/programs were defined. With the help of analysis of nature dependencies related to the strategic aspect of the project, an increase of initial costs of the long-term and high-risk projects had also been described.